Cultural Expression in Batik: An Analysis of Writing and Motifs - Rizal Fauzi; Mia Maarif (Universitas Serang Raya, 2024)
Problems: This study aims to explore the role of batik as a medium of cultural expression by focusing on the analysis of motifs and writing about batik. The primary issue addressed is how batik motifs, such as